Mass Media and the Political Parties in Indonesia In the 2007-2008 Period - Dwi Tiyanto (Department of Communication Studies, Faculty of Social and Political Sciences Universitas, 2008)
The study deals with three issues i..e how the mass media especially print in Indonesia represent political party in the period of 2007-2008 prior to the 2009 general election, what the public think of the performance of political party, and which sources the public acces to get information about political parties’ performance. The survey and in-depth interview are used in the study focuses in Solo Central Java. The study suggests that the mass media often represent political party negatively and the public tends to think the performance of politial party negatively as well. The public mostly get information on politics including political party from the mass media especially television and print media.